Eating disorders among adolescent female students in Jeddah, Saudi Arabia - Almutairi, Reem; Ariffin, Ahmad Azuhairi; Mahmud, Aidalina; Dablool, Anas S. (Universiti Sains Malaysia Press, 2023)
Background: Eating disorders (EDs) are characterised by an abnormal attitude towards food that causes someone to change their eating habits and behaviour. This study aimed to investigate the prevalence of EDs and their associated factors among female going-school adolescents in Jeddah, Saudi Arabia. Methods: A cross-sectional study was conducted in five schools in Jeddah, Saudi Arabia, among a representative random sample of female adolescent students aged 13 years old– 18 years old. A simple random sampling method was used to select the participants. An online selfadministered questionnaire, the Arabic version of eating attitude test (EAT-26) and socio-cultural attitudes toward appearance questionnaire (SATAQ-4), was used. Results: More than half (53.6%) of adolescent girls scored at or above the cut-off point of EAT-26. Around 45% of the participants had experienced family influence on their appearance and body shape, 36.7% had experienced peer influence on these factors, and 49.4% had experienced media influence. Family influence was significantly associated with EDs (P = 0.013). Conclusion: The high prevalence of EDs among female going-school adolescents in Jeddah, Saudi Arabia, is of great concern. To mitigate this problem, effective programmes must be designed to change their dietary habits while considering the effects of family, peer and media influence, as well as focusing on the importance of eating breakfast and practising physical activity.